Expression of DDX5 and DDX17 in ovarian cancer tissues and their effects on proliferation and drug resistance of human ovarian cancer cell line SKOV3 - HUANG Jie, LI Runbo, GUO Jianxin, HAN Jian (Jichu yixue yu linchuang, 2023)
Objective To analyze the expression of DDX5 and DDX17 in ovarian cancer and their relationship with patient survival, and to study the effects of DDX5 and DDX17 on proliferation and drug resistance of ovarian cancer cell line SKOV3. Methods The expression of DDX5 and DDX17 was detected by RT-qPCR in tissue samples from 40 cases of ovarian carcinoma and 27 controls. TCGA database was used to analyze the relationship between DDX15/DDX17 and survival prognosis of ovarian cancer patients. The expression of DDX5 and DDX17 in SKOV3 was down-regulated by lentivirus-mediated DDX5-shRNA and DDX17-shRNA. Western blot was used to verify the knockdown effect, and CCK8 was used to detect cell proliferation and resistance to paclitaxel and carboplatin. Results Compared with normal ovarian epithelium, the expression of DDX5 in samples from ovarian carcinoma was increased, while that of DDX17 was decreased significantly(P＜0.05); Ovarian cancer patients with high DDX5 expression had shorter progression-free survival and overall survival time, while those with high DDX17 expression had longer progression-free survival and overall survival time. Down-regulated DDX5 expression inhibited the SKOV3 cells proliferation, while down-regulated DDX17 expression promoted SKOV3 cells proliferation. The drug sensitivity of SKOV3 cells to paclitaxel and carboplatin was significantly increased after the down-regulation of DDX5 expression, while the drug sensitivity of SKOV3 cells to paclitaxel and carboplatin was not significantly changed after the down-regulation of DDX17 expression. Conclusions DDX5 and DDX17 regulate proliferation and drug resistance of ovarian cancer cells, and are potential regulatory factors functioning in ovarian cancer.